Accommodation of Customs and Islamic Laws in Determining the Beginning of the Month of Ramadan for Indigenous Papuan Muslim Community in West Papua - Sudirman Sudirman; Ahmad Sanuwari Long; Hasse Jubba (Jurnal Ilmiah Al-Syir'ah, 2022)
The focus of this research is to examine the accommodation of Islamic custom and law, especially in determining the beginning and end of the month of Ramadan in indigenous Papuan Muslim communities in West Papua. This determination method is known as the traditional method, which is considered the most accurate in determining the beginning of the month of Ramadan. The community also maintains this method even though it often differs from the government's determination. The analytical method used in this research is phenomenology by looking at people's behaviour as text that can be interpreted and given meaning. The data used as the basis for the analysis of this study were obtained from observations, interviews, and documentation. Observations focused on indigenous peoples' traditions in determining the beginning and end of non-Ramadan. Interviews were conducted with 12 informants of syarak judges (Imam, khatib, muazzin, and marbot) who have knowledge and actors in the traditional method. The study results show that the indigenous people have been practising determining the beginning and end of the month of Ramadan for a long time, carried out by syarak judges consisting of imams, khatib, muazzin, and marbot. They are figures who are considered capable of knowing when the month of Ramadan will arrive. As for the number of days of Ramadan, it must be 30 days, so since the first day is set, it will be counted up to the 30th day. The number of days cannot be less and cannot be more. The limitation of this research lies in the limited time in the research process because it was carried out when there was an outbreak of the Corona Virus Disease 19.